143k views
1 vote
F r(x) = 3x – 1 and s(x) = 2x + 1, which expression is equivalent to ?

F r(x) = 3x – 1 and s(x) = 2x + 1, which expression is equivalent to ?-example-1
User Jquintana
by
5.9k points

2 Answers

2 votes

Answer:

Choice A is correct answer.

Explanation:

We have given two functions.

r(x) = 3x – 1 and s(x) = 2x + 1

We have to find the quotient of the given two functions.

(r/s)(x) = ? and (r/s)(6) = ?

The formula to find the quotient is:

(r/s)(x) = r(x) / s(x)

Putting given values in above formula, we have

(r/s)(x) = 3x-1 / 2x-1

Putting x 6 in above equation, we have

(r/s)(6) = 3(6)-1 / 2(6)-1 which is the answer.

User Millport
by
5.4k points
3 votes

Answer: The first option.

Explanation:

You have the following functions:


r(x)=3x-1\\s(x)=2x+1

You have that
((r)/(2)) indicates the following:


((r)/(s))=(3x-1)/(2x+1)

Now, you must substitute x=6, then you obtain:


((r)/(s))(6)=(3(6)-1)/(2(6)+1)

Therefore the answer is the first option.

User Greyshack
by
5.5k points